The President's Page. (Exceptional Children, 1962)
The article comments on the development of the 1962 International Council for Exceptional Children Convention (CEC) in the U.S. There are various changes occurred in the 1962 programming; there were fewer sectional meetings than in the 1961 program and at one afternoon meeting only six large section meetings were held. The convention hoped that teachers, professors, research specialists and others among the membership of CEC would seek the opportunity to present their problems, their ideas, their methods, results of new research and demonstration projects, to the participants.